2018
DOI: 10.1016/j.jtcvs.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

The importance and ways of exploring the entire chest before and after cardiac surgery: Chest radiography, lung ultrasonography, and computed tomography

Abstract: Flow chart on use of chest radiography, CT, and chest ultrasonography in cardiac surgery. Central MessageChest radiography is a fundamental tool in cardiac surgery, but it may be replaced by CT preoperatively, at least in selected cases, and by LUS to monitor common postoperative pulmonary complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…(Ann Thorac Surg 2020;109:178-84) Ó 2020 by The Society of Thoracic Surgeons L ung ultrasound (LUS) is a noninvasive, easy, and fast technique for the evaluation of pulmonary disease in children, especially in the acute setting. [1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…(Ann Thorac Surg 2020;109:178-84) Ó 2020 by The Society of Thoracic Surgeons L ung ultrasound (LUS) is a noninvasive, easy, and fast technique for the evaluation of pulmonary disease in children, especially in the acute setting. [1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Pulmonary complications are common with pediatric cardiac surgery and have been evaluated primarily with chest roentgenograms. [4][5][6][7] Recent studies have evaluated the utility of LUS in children undergoing congenital heart surgery. [4][5][6][7] These studies have shown diagnostic accuracy of LUS for pulmonary complications after surgery including pleural effusion, atelectasis, pneumothorax, and pneumonia.…”
mentioning
confidence: 99%
See 3 more Smart Citations